Emperor of sand [compact disc] (Reprise, 2017)
A deeply imaginative and complex conceptual storyline that ponders the nature of time. Threading together the myth of a man sentenced to death in a majestically malevolent desert, the band conjures the grains of a musical and lyrical odyssey slipping quickly through a cosmic hourglass.